(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
With the advent of internet and internet based media, electronic word of mouth has gained prominence in influencing consumer decision. An exploratory study using qualitative analysis has been conducted in the hospitality industry in order to understand the trends in the generation of electronic content in hotel reviews by customers. Two hundred positive and an equal number of negative reviews of a top brand hotel have been explored in the order of appearance in a popular accommodation website. The analysis indicated that customers are more eloquent in describing positive aspects, overall evaluations and positive overall evaluations than negative aspects, attribute based evaluations and negative overall evaluations. Negative evaluations are more based on specific attributes than overall evaluations. The adjectives and verbs used in describing a positive evaluation are found to be more compared to negative evaluation. The findings are at variance with some of the earlier studies. These findings are of practical relevance to hoteliers in focusing their marketing and operation efforts.